Implementasi Model Pembelajaran Kontekstual Untuk Meningkatkan Hasil Belajar Penjasorkes Materi Jurus Tunggal Pencak Silat - Gusti Ngurah Arya Yudaparmita (Edukasi: Jurnal Pendidikan Dasar, 2020)
This study aims to improve the learning outcomes of pencak silat single moves through the implementation of contextual teaching and learning. This type of research is Classroom Action Research. This research was conducted in 2 cycles with the design cycle consisting of planning, implementation, observation/evaluation and reflection. The research subjects were students of grade VI of SD Negeri 3 Pekutatan. Based on the results of data analysis the percentage of mastery learning outcomes in the first cycle amounted to 81.25% (an increase in cycle II to 93.75%. The average percentage of cycle I and II amounted to 87.5% with a good category, which means mastery learning mastery single pencak silat is said to be complete because it meets the KKM classically that is ≥ 67%. The conclusion is that the learning outcomes of pencak silat single increases through the implementation of contextual teaching and learning. Keywords: contextual teaching and learning, learning outcomes, single pencak silat